Assessing the Changes of Mumps Characteristics with Different Vaccination Strategies Using Surveillance Data: Importance to Introduce the 2-Dose Schedule in Quzhou of China - Chunting Zhou; Wei Song; Zhiying Yin; Sheng Li; Xiaoying Gong; Quanjun Fang; Shuangqing Wang (Journal of Immunology Research)
Background. From 2005 to 2016, the prevention and control of mumps in China have undergone three stages of transition. These include the use of MuCV as a self-supported vaccine, the introduction of one-dose MMR to the Expanded Program on Immunization (EPI), and the administration of two-dose MuCV following supplementary immunization activities (SIAs) using MM. Here, using surveillance data, we assessed the epidemiology of mumps during the three stages. Methods. Children in Quzhou of China born from 2005 to 2016 and registered in the Zhejiang Provincial Immunization Information System (ZJIIS) were included. We analyzed the epidemic data and calculated incidence and MuCV coverage via birth cohorts. Results. The average incidence of mumps in 2005-2006, 2007-2010, and 2011-2016 was 51.57, 41.02, and 12.53 per 100,000 individuals, respectively. The highest incidence was in children aged 6-14 years from 2005-2016, of which the majority were school students (67.84%). Approximately 90% of the reported outbreaks occurred in school children (primary school/middle school). The seasonal characteristics of mumps were less obvious from 2011 to 2016. The coverage of one-dose MMR in the 2005 birth cohort was 71.38%. For the 2006-2010 birth cohort, the coverage of one-dose MuCV was 96.82% and the coverage of two-dose MuCV was 17.68%. The children born from 2011 to 2016 were only free vaccinated with MMR; the coverage of one-dose MuCV was 99.10%. The mumps incidence in the three birth cohorts significantly declined (X2=805.90, P<0.001 for trend). Except the children less than two years old, the mumps incidence for the children born from 2006 to 2010 was higher than that for the children born from 2011 to 2016. Conclusion. The mumps incidence significantly declined following the introduction of one-dose MMR. The SIA using MM led to a rapid reduction of mumps cases. Therefore, we recommend a two-dose MuCV routine immunization schedule and improved vaccination coverage.